Management Information Systems / Organization and Technology in the Networked Enterprise: Sixth Edition - Laudon Jane Price; Laudon Kenneth C (Prentice Hall International, 2000)
This book uses technology to teach students about information systems and technology. Organizational Foundations of Information Systems, The Information Systems Revolution: Transforming Business and Management, The Strategic Role of Information Systems, Ethical and Social Impact of Information Systems, Technical Foundations of Information Systems, Computers and Information Processing, Information Systems Software, Managing Data Resources, Telecommunications and Networks, Building Information Systems: Contemporary Approaches, Approaches to Systems-Building, System Success and Failure: Implementation, Management and Organizational Support Systems, Managing Knowledge, Enhancing Management Decision Making, Managing Contemporary Information Systems, Information Systems Security and Control, Managing International Information Systems, Managing Firm Infrastructure and Enterprise Systems, References, Index.